2016
DOI: 10.1007/s11948-016-9803-0
|View full text |Cite
|
Sign up to set email alerts
|

Review of Instructional Approaches in Ethics Education

Abstract: Increased investment in ethics education has prompted a variety of instructional objectives and frameworks. Yet, no systematic procedure to classify these varying instructional approaches has been attempted. In the present study, a quantitative clustering procedure was conducted to derive a typology of instruction in ethics education. In total, 330 ethics training programs were included in the cluster analysis. The training programs were appraised with respect to four instructional categories including instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 109 publications
0
42
1
3
Order By: Relevance
“…Alongside such quantitative research, it would be important to conduct qualitative research to better understand the contexts, facilitators and barriers to the development of PHE education as well as the effectiveness of different educational methods. Indeed, we would argue that what is missing is a comparative analysis of educational methods in PHE instruction, similar to the study by Mulhearn et al (2016). For a field that Bhas been slow to meet this educational responsibility^ (Tulchinsky et al 2015: 2), promoting more effective educational methods can be a good way to foster ethics education in PH.…”
Section: Resultsmentioning
confidence: 83%
“…Alongside such quantitative research, it would be important to conduct qualitative research to better understand the contexts, facilitators and barriers to the development of PHE education as well as the effectiveness of different educational methods. Indeed, we would argue that what is missing is a comparative analysis of educational methods in PHE instruction, similar to the study by Mulhearn et al (2016). For a field that Bhas been slow to meet this educational responsibility^ (Tulchinsky et al 2015: 2), promoting more effective educational methods can be a good way to foster ethics education in PH.…”
Section: Resultsmentioning
confidence: 83%
“…But in this case, on further of online counseling development have some conditions which must be observed by counselors as an actor these services, ethics in the implementation of online counseling services (Kawabata & Tamura, 2007;Lu et al, 2013;Mulhearn et al, 2017;Musiat et al, 2014;Richards & Viganó, 2013;Seligman & Reichenberg, 2015). Kraus (Kraus et al, 2010) suggested that the ethics here contains the meaning which associated with the principle propriety, righteousness, as well as the behaviors that is acceptable in a relationship of humanity.…”
Section: Ethical Issues In Online Counselingmentioning
confidence: 99%
“…In implementation and development, there are several pros and cons related to aspects of the online counseling, but this model is a great potential to be developed (Ardi & Yendi, 2013;Avery et al, 2014;Gackenbach, 2011;Rodda et al, 2013;Ziomek-Daigle & Curtis, 2017). The important thing to concern for online counseling service implementation is the ethics of service embodied in a particular code of ethics (Kawabata & Tamura, 2007;Lu, Chang, & Yu, 2013;Mulhearn et al, 2017;Musiat, Goldstone, & Tarrier, 2014;Richards & Viganó, 2013;Seligman & Reichenberg, 2015). The need for caution with regard to the code of ethics is based on findings from Shaw and Shaw that in 2002 there were 88 counseling website, which only 88% of them list the full name of the counselors with 75% who has qualified counselors, then 49% use the assessment procedure and only 27% use the security software has encrypted (McLeod, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, con técnicas como la Midstrem Modulation (regulación de mitad de camino), donde un humanista se integra e interactúa con los 2019, Universitat Politècnica de València Congreso In-Red (2019) investigadores para involucrarlos con los aspectos sociales y éticos de su trabajo (Flipse et al, 2013). Mulhearn et al (2017) en un extenso meta-análisis de metodologías docentes aplicadas a la adquisición de esta competencia observaron que los tipos de aproximación más habitual son la discusión general y adherencia a la norma. El primer tipo generalmente se aborda mediante discusiones en grupos de tamaño variable, mientras el segundo, más basado en moral filosófica, se aborda mediante clases magistrales.…”
Section: Introductionunclassified